Sistema Primario de Par Torsional para la Calibración de Transductores (2017)
The project was developed as solution to the need of the company Calibration Service S.A.S., which was needing of an equipment of calibration for his transducers of torsional couple. Likewise, it was looked by the development of the project, the creation of a new service of calibration. For the development of the project, it began with the summary of information and description of the current situation in the country and in the world. During the search of information, one possessed the support of Metrología's National Center of Mexico (CENAM), which allowed to know, to learn and to conceive the general idea for the development of the project. Later, the basic parameters of design were established and the conceptual processes of measurement were evaluated. Then there was realized the detailed design, by which the different elements of the system were calculated. Later there was realized the simulation and modeling of the pieces, this step allowed to check the calculations realized in the detailed design. Finally there were elaborated the planes, the manuals and the financial analysis of the project.